The Role of Islamic Banking in Supporting Women's Economic Empowerment - Trimulato, Trimulato; Syarifuddin, Syarifuddin (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
AbstractPurpose -. This study describes the development of productive and consumptive Islamic bank financing. As well as explaining the role of Islamic banks in supporting women's economic empowerment.Method - This type of research is a literature study using qualitative. The data source in this research is secondary data that certain institutions have presented. The data collection technique used in this research is literature from various sources relevant to the research theme. Both from journals, books, and other library sources. The data analysis technique used in this research is descriptive qualitative, which shows the development of Islamic bank financing, as well as the form of empowerment that can be done by Islamic banks in supporting the women's economy.Result- The results of this study show that Islamic bank financing grew by 3.41 percent and that the portion of Islamic bank financing is still dominated by consumptive financing, not productive. Islamic banks need to increase productive financing, especially for women's economic empowerment. Islamic banks have a role in increasing women's productive financing with their profit-sharing system, as well as their social funds, and can collaborate with various parties.Implication - This study uses data from Islamic banks in Indonesia. The Financing for Consumptive and Productive Product. Financing for women's economic especially in one Islamic Bank. Originality- The paper looks financing distribution in Indonesia. Product Financing in Islamic Bank. Islamic banks need to be encouraged to activities that support the real sector.Keywords:    Islamic Banking, Supporting, and Women’s Economic